Positive Leadership and Employee Well-Being. (February 2013) - Kelloway, E. Kevin; Weigand, Heidi; McKee, Margaret C.; Das, Hari
We report two studies examining the relationship between positive leadership behaviors and employee well-being. In the first, data from 454 nursing home employees showed that (a) a newly developed measure of positive leadership was distinct from transformational leadership and (b) positive leadership behaviors predicted context-specific and context-free well-being after controlling for transformational and abusive leadership. In the second study, data from a daily diary study ( N = 26) showed that (a) positive leadership predicted positive, but not negative, employee affect and (b) positive leadership interacted with transformational leadership to predict employees positive affect.